Chronic fatigue: psychometric properties and updated norm values of the Chalder fatigue scale in a cross-sectional sample representative of the German population - Lina Krakau; Felix Wicke; Winfried Häuser; Manfred E. Beutel; Elmar Brähler; Nora Hettich-Damm (Annals of Medicine)
Background The Chalder Fatigue Scale (CFQ) is a commonly used self-report instrument assessing the severity and chronicity of fatigue. We examine the psychometric properties of the CFQ and provide updated normative data for the German general population.Materials and Methods The CFQ was administered to N = 2519 participants (16-96 years). Statistical analyses included the evaluation of the item properties, confirmatory factor analysis and examinig associations with mental health and sociodemographic data. CFQ cut-offs were used to estimate proportions of severe and chronic fatigue scores. We calculated percentile norms for the total sample and stratified by age groups and gender.Results Indicators of internal consistency reliability were high for the CFQ total and subscales (α = 0.84–0.94; ω = 0.86–0.95). We found excellent model fit for a one (χ2 = 196.011, df = 44, p ≤ .001; CFI=.991, RMSEA = 0.037, SRMR = 0.059) and two-factor solution (χ2 = 115.055, df = 42, p ≤ .001; CFI=.996, RMSEA = 0.026, SRMR = 0.045). The CFQ total scale showed low to moderate associations with depression (r = .49, p ≤ .001), anxiety (r = .45, p ≤ .001), and loneliness (r = .26, p ≤ .001), indicating acceptable discriminant validity. Current unemployment was a relevant sociodemographic correlate of fatigue severity (CFQ total: β =.38, se =.09, p ≤ .001). 14.2% of participants reported severe fatigue, while 4.3% reported being fatigued for at least six months (chronic fatigue).Conclusion The CFQ is a brief and reliable instrument for assessing fatigue in general population settings. The results are limited by the lack of comparison with other established fatigue questionnaires.